Donizete Galvão, Orides Fontela e o “reino do poeta” - Ivan Marques (Estudos de Literatura Brasileira Contemporânea, 2014)
This paper compares the works of two representative recent Brazilian poets, Donizete Galvão (1955-2014) and Orides Fontela (1940-1998). From the analysis of a poem written by Donizete in honor of Orides, on the occasion of her death, included in the book Ruminações (1999), the text raises and discusses characteristics that are common to both works, especially the contamination of limpid poetry and search of the sacred (long-awaited by both authors) by the harshness of reality and the impurities of matter that served as the basis for their poems.